Orbital alignment as a key determinant of nanotransport in molecular tunnel junctions despite fermi level pinning: exponential correlation with molecule-electrode coupling - Bâldea, Ioan; Xie, Zuoti (The journal of physical chemistry letters, 2025)
At first glance, interrogating the impact of molecular orbital alignment on charge transport in molecular tunnel junctions may appear out of place, given the well-documented strong Fermi level pinning effect. To demonstrate that the contrary is true, we investigated molecular junctions based on self-assembled monolayers (SAMs) of alkyl monothiols (CnT) and dithiols (CnDT) with Ag, Au, and Pt electrodes using the conducting probe atomic force microscopy (CP-AFM) platform. Analysis of these data reveals that the HOMO-metal electronic coupling Γ and the low bias conductance G are exponentially correlated with the HOMO energy offset relative to the Fermi level ε0 = EMO - EF (Γ ∝ exp(−α̅|ε0|), G ∝ exp(−α|ε0|), α ≈ 2α̅). This impact is remarkably strong: for CnT junctions, a reduction by only 25% in |ε0| translates into an increase of Γ by 1 order of magnitude and of G by 2 orders of magnitude. More broadly, this exponential correlation of Γ and G with ε0 offers deeper insight into nanotransport and extends understanding of the previously reported exponential dependence of Γ and G on the SAM-induced work function shift ΔΦ, which reflects the linear correlation between ε0 and ΔΦ. From a fundamental perspective, it is crucial to highlight that our data validate a formula for Γ (a property which depends on both electrodes of a junction), which features (i) ε0 rather than ΔΦ (i.e., a property of a full junction versus a property of a “half a junction”) and (ii) ε0 rather than its square root in the exponent, thereby invalidating the widely employed tunneling barrier picture.
Gesehen am 19.01.2026